Origins of the School Mediation Programs: Different approaches that influence this restorative practice - Pulido, Rosa; Martín Seoane, Gema; Lucas Molina, Beatriz (Anales de Psicología / Annals of Psychology, 2013)
The objective of the present article is to analyze the origins of school mediation and the disciplines that support it. A better knowledge of these different approaches and the terminology related (restorative justice, cooperative groups, supporting students, etc.) allows a broader understanding of its possibilities. To achieve this objective, a literature review was conducted: of aboriginal groups who use a concept of conciliation within their community, the incorporation into the judicial system, in addition to other areas that have influenced the development of mediation programs in educational settings, such as cooperative learning and peer support programs. Finally conclusions are presented, analyzing the contributions of each approach, which will result in better implementation of this intervention approach.